ENGOT-EN20/GOG-3083/XPORT-EC-042 - A phase III, randomized, placebo-controlled, double-blind, multicenter trial of selinexor in maintenance therapy after systemic therapy for patients with p53 wild-type, advanced, or recurrent endometrial carcinoma: rationale, methods, and trial design - Vergote, Ignace; Perez Fidalgo, Alejandro; Valabrega, Giorgio; Monk, Bradley J; Herzog, Thomas; Cibula, David; Colombo, Nicoletta; Pothuri, Bhavana; Sehouli, Jalid; Korach, Jacob; Barlin, Joyce; Papadimitriou, Christos A; et al. (International journal of gynecological cancer, 2024)
BACKGROUND: Patients with advanced/recurrent endometrial cancer have a poor prognosis and limited treatment options. Biomarkers such as tumor protein 53 (TP53) in endometrial cancer can integrate novel strategies for improved and individualized treatment that could impact patient outcomes. In an exploratory analysis of the phase III ENGOT-EN5/GOG-3055/SIENDO study of selinexor maintenance monotherapy 80 mg in advanced/recurrent endometrial cancer, a pre-specified subgroup of patients with TP53 wild type (wt) endometrial cancer showed preliminary activity at long-term follow-up with a generally manageable safety profile (median progression-free survival 27.4 months vs 5.2 months placebo, HR=0.41). PRIMARY OBJECTIVE: To evaluate the efficacy of selinexor compared with placebo as maintenance therapy in patients with advanced or recurrent TP53wt endometrial cancer. STUDY HYPOTHESIS: Selinexor administered at 60 mg weekly as maintenance therapy will show manageable safety and maintain efficacy in patients with TP53wt advanced/recurrent endometrial cancer after systemic therapy versus placebo. TRIAL DESIGN: This is a prospective, multicenter, double-blind, placebo-controlled, randomized phase III study designed to evaluate the efficacy and safety of selinexor as a maintenance therapy in patients with advanced or recurrent TP53wt endometrial cancer. MAJOR INCLUSION/EXCLUSION CRITERIA: Eligible patients must have histologically confirmed endometrial cancer, TP53wt confirmed by next-generation sequencing, completed at least 12 weeks of platinum-based therapy with or without immunotherapy, with confirmed partial response or complete response, and primary Stage IV disease or at first relapse. PRIMARY ENDPOINT: The primary endpoint is investigator-assessed progression-free survival per Response Evaluation Criteria in Solid Tumors (RECIST) v1.1 in the intent-to-treat population. SAMPLE SIZE: A total of 220 patients will be enrolled. ESTIMATED DATES FOR COMPLETING ACCRUAL AND PRESENTING RESULTS: Accrual is expected to be completed in 2024 with presentation of results in 2025. TRIAL REGISTRATION: NCT05611931.
Keywords: Humans; multicentrické studie jako téma; Double-Blind Method; nádorový supresorový protein p53; Female; udržovací chemoterapie; Endometrial Neoplasms; lidé; dvojitá slepá metoda; Triazoles; randomizované kontrolované studie jako téma; Uterine Cancer; Maintenance Chemotherapy; ženské pohlaví; Randomized Controlled Trials as Topic; nádory endometria; triazoly; lokální recidiva nádoru; Hydrazines; Clinical Trials, Phase III as Topic; Neoplasm Recurrence, Local; hydraziny; Multicenter Studies as Topic; klinické zkoušky, fáze III jako téma; Tumor Suppressor Protein p53